Real‐time intrafraction prostate motion during linac based stereotactic radiotherapy with rectal displacement. (27th September 2017) - Legge, Kimberley; Nguyen, Doan; Ng, Jin Aun; Wilton, Lee; Richardson, Matthew; Booth, Jeremy; Keall, Paul; O'Connor, Darryl J; Greer, Peter; Martin, Jarad
Abstract: Background: Kilovoltage Intrafraction Monitoring (KIM) is a method which determines the three‐dimensional position of the prostate from two‐dimensional kilovoltage (kV) projections taken during linac based radiotherapy treatment with real‐time feedback. Rectal displacement devices (RDDs) allow for improved rectal dosimetry during prostate cancer treatment. This study used KIM to perform a preliminary investigation of prostate intrafraction motion observed in patients with an RDD in place. Methods: Ten patients with intermediate to high‐risk prostate cancer were treated with a Rectafix RDD in place during two boost fractions of 9.5–10 Gy delivered using volumetric modulated arc therapy (VMAT) on Clinac iX and Truebeam linacs. Two‐dimensional kV projections were acquired during treatment. KIM software was used following treatment to determine the displacement of the prostate over time. The displacement results were analyzed to determine the percentage of treatment time the prostate spent within 1 mm, between 1 and 2 mm, between 2 and 3 mm and greater than 3 mm from its initial position. Results: KIM successfully measured displacement for 19 prostate stereotactic boost fractions. The prostate was within 1 mm of its initial position for 84.8%, 1–2 mm for 14%, 2–3 mm 1.2% and ≥3 mm only 0.4% of the treatment time. Conclusions: In this preliminary study using KIM, KIM was successfully used to measure prostate intrafraction motion, which was found to be small in the presence of a rectal displacement device. Trial registration: The Hunter New England Human Research Ethics Committee reference number is 14/08/20/3.01.